Legal capacity, mental capacity and supported decision-making: Report from a panel event. (January 2019) - Craigie, Jillian; Bach, Michael; Gurbai, Sándor; Kanter, Arlene; Kim, Scott Y.H.; Lewis, Oliver; Morgan, Graham
Abstract: Against a backdrop of the UN Convention on the Rights of Persons with Disabilities having been in place for over a decade, discussions about legal capacity, the relevance of mental capacity and the shift to supported decision-making, continue to develop. A panel event was held at the King's Transnational Law Summit in 2018 with the aim of understanding the contours of the dialogue around these issues. This paper presents the contributions of the panel members, a summary of the discussion that took place and a synthesis of the views expressed. It suggests that divergent conclusions in this area turn on disagreements about: the consequences of sometimes limiting legal capacity for people with mental disabilities; the emphasis placed on particular values; the basis for mental capacity assessments; and the scope for supported decision-making. It also highlights the connection between resources, recognition and freedoms for people with mental disabilities, and therefore the issues that arise when discussion in this area is limited to legal capacity in the context of decision-making.